2021
DOI: 10.1108/jme-05-2021-0062
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of racism in Spanish music textbooks: a real path towards interculturality through images?

Abstract: Purpose An analysis of the images in music education textbooks for primary education has shown how the images do not fully reflect the human diversity present in the classroom and, therefore, continue to perpetuate positions that can lead to racism. The purpose of this paper is the analysis of the images to carried out has demonstrated how little progress has been made in the representation of diversity and how, in the 21st century, stereotypes continue to persist in the representation of cultural diversity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In relation to the latter, these works provide evidence of the existence of gender stereotypes in textbooks, both in the Spanish context Bernabé and Martínez-Bello, 2018) and in the international context (Koza, 1994). Likewise, there is evidence of how textbooks do not sufficiently reflect the ethnic diversity present in the classroom (Bernabé & Martínez-Bello, 2021). Other studies, also related to the field of study of textbooks in music education, refer to new technologies (ICTs).…”
Section: Theoretical Frameworkmentioning
confidence: 96%
“…In relation to the latter, these works provide evidence of the existence of gender stereotypes in textbooks, both in the Spanish context Bernabé and Martínez-Bello, 2018) and in the international context (Koza, 1994). Likewise, there is evidence of how textbooks do not sufficiently reflect the ethnic diversity present in the classroom (Bernabé & Martínez-Bello, 2021). Other studies, also related to the field of study of textbooks in music education, refer to new technologies (ICTs).…”
Section: Theoretical Frameworkmentioning
confidence: 96%
“…In relation to the latter, these works provide evidence of the existence of gender stereotypes in textbooks, both in the Spanish context and in the international context (Koza, 1994). Likewise, there is evidence of how textbooks do not sufficiently reflect the ethnic diversity present in the classroom (Bernabé & Martínez-Bello, 2021). Other studies, also related to the field of study of textbooks in music education, refer to new technologies (ICTs).…”
Section: Theoretical Frameworkmentioning
confidence: 98%
“…In addition, this research aims to fill an existing gap in the scientific literature regarding the analysis of textbooks in the field of music at national level, where we found research that covers the textbook as a didactic mediator in music education (Ahijado et al, 2019; Gual & Salas, 2020), analyse racism (Bernabé & Martinez-Bello, 2021), the figure of women (Bernabé-Villodre & Martínez-Bello, 2018; Bernabé-Villodre et al, 2021) and Krusian origin for the teaching of aesthetics and the history of music in Spain (de Andrés, 2011), but no works are found that analyse the discourses on the history of music that these present. On the other hand, there are studies in other areas that analyse the narrative of textbooks, such as work developed by Gómez Carrasco et al (2015) on the construction of a national narrative in history textbooks in Spain, the study conducted by Padilla and Vana (2022) who carried out a critical discourse analysis and a visual analysis in Spanish language textbooks to examine the representation of Afro-Latinxs and the ideologies behind these representations.…”
Section: Introductionmentioning
confidence: 99%